2017
DOI: 10.1007/s00216-017-0520-6
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the peptide retention mechanism in molecularly imprinted polymers

Abstract: Molecularly imprinted polymers (MIPs) have been used as useful sorbents in solid-phase extraction for a wide range of molecules and sample matrices. Their unique selectivity can be fine-tuned in the imprinting process and is crucial for the extraction of macromolecules from complex matrices such as serum. A relevant example of this is the application of MIPs to peptides in diagnostic assays. In this article the selectivity of MIPs, previously implemented in a quantitative mass-spectrometric assay for the bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the past decade, the number of studies toward using MIPs as a biomarker has increased, as they hold a potential to provide a sensitive, undamaged, rapid and low-cost diagnostic tool [80]. The detection of serum albumin [81,82], hemoglobin [83,84], ferritin [85] and avidin [86], as well as studies of infectious diseases [87][88][89], bone loss [90,91], cardiovascular diseases [92] and various cancers are some areas [4,[93][94][95][96][97][98][99][100][101][102] that are of high interest for the use of MIPs as biomarkers.…”
Section: Mips and Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, the number of studies toward using MIPs as a biomarker has increased, as they hold a potential to provide a sensitive, undamaged, rapid and low-cost diagnostic tool [80]. The detection of serum albumin [81,82], hemoglobin [83,84], ferritin [85] and avidin [86], as well as studies of infectious diseases [87][88][89], bone loss [90,91], cardiovascular diseases [92] and various cancers are some areas [4,[93][94][95][96][97][98][99][100][101][102] that are of high interest for the use of MIPs as biomarkers.…”
Section: Mips and Biomarkersmentioning
confidence: 99%
“…Cancer biomarkers have become more compelling over the past decade because they provide early diagnostics, which increases survival. Pyruvic acid, SA, pro gastrin releasing peptide, p53, carbohydrate antigen 15-3, CEA, PSA, EGFR and VEGF are some of the cancer biomarkers that have been studied by using the molecular imprinting technique [4,[93][94][95][96][97][98][99][100][101][102].…”
Section: Mips and Biomarkersmentioning
confidence: 99%
“…In respect of interference from matrix components, the mMIP is likely to interact with many abundant tryptic peptides in the matrix, as has been observed previously for MIPs with similar compositions targeting NLLGLIEAK. 7 , 32 It is expected that use of mMIPs with higher binding capacities will yield higher recoveries despite nonspecific interactions of the matrix components (N.B. mMIP C was synthesized using a template to cross-linker mole ratio in the feed of 1:533, thus there is significant scope for preparing mMIPs with significantly higher binding capacities, if desired, by increasing the template to cross-linker ratio during the polymer synthesis stage).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, a number of studies have been reported attempting to correlate molecular descriptors with MIP binding data using a range of multivariate tools. Rossetti et al employed PLS models to correlate molecular descriptors with solid-phase extraction retention data for a series of biomarker pro-gastrin-releasing peptides in order to elucidate the recognition mechanism [ 670 ]. Liu et al used MLR and PCA to couple structural and molecular parameters of a quercetin MIP to its adsorption selectivity [ 671 ].…”
Section: Mip Structure and Functionmentioning
confidence: 99%